2021
DOI: 10.4102/sajhrm.v19i0.1636
|View full text |Cite
|
Sign up to set email alerts
|

Constructive interpersonal leadership relations in knowledge-based organisations: A theoretical framework

Abstract: Orientation: Acknowledging the need for a deeper understanding of interpersonal communication as part of interpersonal leadership in knowledge-based organisational contexts.Research purpose: This study aimed to propose a theoretically based definition of constructive interpersonal leadership relations (ILRs) and a generic model of ILR with guidelines for fostering constructive ILR in knowledge-based contexts.Motivation for the study: Emerging trends showed knowledge-based organisations presented unique sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Such findings are consistent with those of Williams et al (2011) and Mulika and Routray (2016) who have all identified unwanted interferences that undermine the fight against rural unemployment challenges, transformation or the sustainability of local livelihoods. This is also consistent with Louw and Barker (2021), as well as Gorgens-Ekermans and Roux's (2021) assertion that leaders influence those they lead.…”
Section: Rural and Cultural-based Communication Processessupporting
confidence: 86%
“…Such findings are consistent with those of Williams et al (2011) and Mulika and Routray (2016) who have all identified unwanted interferences that undermine the fight against rural unemployment challenges, transformation or the sustainability of local livelihoods. This is also consistent with Louw and Barker (2021), as well as Gorgens-Ekermans and Roux's (2021) assertion that leaders influence those they lead.…”
Section: Rural and Cultural-based Communication Processessupporting
confidence: 86%
“…The main limitations of the study are that its findings are bound to be affected by the issue of transferability, since they were generated from employees' perceptions and experiences in a specific context and the study was cross-sectional in design as data were collected at a particular point in time. However, Louw (2018) acknowledges that the worthiness of any research is determined by the extent to which it contributes to knowledge, both theoretical and in practice. Hence it is posited that this study is new and unique and contributes to the existing body of knowledge in communication research and organisational communication practice in several ways.…”
Section: Limitations and Strengthsmentioning
confidence: 99%